Effects of proprioceptive neuromuscular facilitation and core stabilization on physical and functional parameters in adolescents with idiopathic scoliosis: a randomized controlled trial - Kaya, Mehmet Hanifi; Buyukturan, Oznur; Buyukturan, Buket; Alkan, Halil; Erbahceci, Fatih (Springer, 2026)
Background Adolescent Idiopathic Scoliosis (AIS) is a three-dimensional spinal deformity that negatively affects postural alignment, functional capacity, and quality of life. Exercise-based interventions such as Proprioceptive Neuromuscular Facilitation (PNF) and Core Stabilization (CS) are increasingly utilized to improve structural and functional outcomes in AIS, yet comparative evidence remains limited. Objective To evaluate and compare the isolated effects of Proprioceptive Neuromuscular Facilitation (PNF) and Core Stabilization (CS) exercises on spinal curvature, trunk rotation, physical function, and health-related quality of life in adolescents with Adolescent Idiopathic Scoliosis (AIS), with the aim of informing evidence-based conservative treatment strategies. Methods This randomized controlled trial included 52 adolescents aged 10-18 years diagnosed with AIS. Participants were randomly assigned to either a PNF group (n = 26) or a CS group (n = 26). Both groups underwent supervised exercise interventions three times per week for 10 weeks. The primary outcome was the Cobb angle. Secondary outcomes included Angle of Trunk Rotation (ATR), Scoliosis Research Society-22 (SRS-22) questionnaire scores, and physical function tests (six-minute walk test, sit-to-stand test). Assessments were conducted by blinded evaluators. Results Both groups demonstrated significant improvements in Cobb angle, ATR, SRS-22 scores, and physical function (p < 0.05). The PNF group showed a greater reduction in Cobb angle (6.8 degrees +/- 1.2 degrees) compared to the CS group (5.4 degrees +/- 1.1 degrees, p < 0.05), as well as superior improvements in ATR. Quality of life and physical performance improved significantly in both groups, with no statistically significant differences between groups in SRS-22 scores. Conclusion Both PNF and CS exercises are effective in improving spinal alignment, trunk symmetry, and physical function in adolescents with AIS. PNF appears to offer greater structural benefits, while both interventions are equally effective in enhancing quality of life. These findings support the integration of exercise-based rehabilitation into conservative management protocols for AIS. Highlights center dot Both PNF and CS exercises significantly improved Cobb angle, trunk rotation, functional capacity, and quality of life in AIS. center dot Improvements in 6-minute walk distance and sit-to-stand test performance paralleled structural changes, indicating that postural correction may also enhance aerobic capacity and physical endurance. center dot Both interventions were effective not only in radiographic correction but also in improving psychosocial well-being, including perceived appearance and overall quality of life.
Keywords: Adolescent Idiopathic Scoliosis; Core Stabilization; Proprioceptive Neuromuscular Facilitation; Cobb Angle; Angle Of Trunk Rotation; Srs-22; Randomized Controlled Trial